Strategic hedging in the Black Sea: The case of Turkey versus Russia. Issue 5 (16th September 2022) - Alim, Eray
Abstract: Although strategic hedging has attracted increasing scholarly attention in the study of how secondary states manage their relations with a neighboring great power, existing works on the subject suffer from a serious defect: privileging unit-level variables over structural determinants and security imperatives. The crux of secondary state hedging, however, is to manage the power imbalance against a local great power and security requirements must therefore be considered as the prime determinant behind decisions to embrace hedging strategies. I shall examine this hypothesis against the empirical evidence provided by the case of Turkey and Russia in the Black Sea region.